2023
DOI: 10.4062/biomolther.2023.002
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol as a Voltage-Gated Sodium Channel Blocker of Peripheral Sodium Channels Nav1.7 and Nav1.5

Abstract: Tramadol is an opioid analog used to treat chronic and acute pain. Intradermal injections of tramadol at hundreds of millimoles have been shown to produce a local anesthetic effect. We used the whole-cell patch-clamp technique in this study to investigate whether tramadol blocks the sodium current in HEK293 cells, which stably express the pain threshold sodium channel Nav1.7 or the cardiac sodium channel Nav1.5. The half-maximal inhibitory concentration of tramadol was 0.73 mM for Nav1.7 and 0.43 mM for Nav1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“… 36 We found also a negative shift in the V 1/2 of activation, and this was also found by Bok et al for Na v 1.7, but not for Na v 1.5. 36 While our findings are thus largely consistent with the study of Bok et al , our study offers significant advances beyond that study by also including other opioids and AP studies in cardiomyocytes. Action potential studies are of particular relevance because previous studies have suggested that tramadol may impact not only on cardiac depolarization and Na v 1.5 current but also on cardiac repolarization and AP duration.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“… 36 We found also a negative shift in the V 1/2 of activation, and this was also found by Bok et al for Na v 1.7, but not for Na v 1.5. 36 While our findings are thus largely consistent with the study of Bok et al , our study offers significant advances beyond that study by also including other opioids and AP studies in cardiomyocytes. Action potential studies are of particular relevance because previous studies have suggested that tramadol may impact not only on cardiac depolarization and Na v 1.5 current but also on cardiac repolarization and AP duration.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the IC 50 on Na v 1.5 channels that were in a partially fast-inactivated state was now 4.5 ± 1.1 μ m , which is close to therapeutic concentrations (up to 1.14 µ m ). This effect was also documented by Bok et al 36 In the meantime, we also notice that this change is not so obvious in the AP measurements in which the cardiomyocytes have a RMP of around −80 mV. Our result showed that the tramadol-induced d V /d t max reduction is concentration dependent, and tramadol-induced reduction of d V /d t max was only present at 300 µ m in comparison to the baseline condition.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations